Growth After the Storm? : A Longer-Run Perspective. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The October 2009 Per Jacobsson Lecture, delivered in Istanbul in conjunction with the 2009 Annual Meetings of the IMF and World Bank, examined the issue of longer-run growth prospects for the global economy following the recent global economic crisis. Will the world be able, in the five to ten years after the crisis abates, to return to the very rapid kind of economic growth sustained in the five years leading up to it? Noting that recent debate on the topic has focused on demand-side factors, neglecting the key area of supply-side sources of growth, Kemal Dervis, the 2009 Per Jacobsson lecturer, argues that contrary to the majority view that limited, below-trend growth is likely to prevail for some time, there is probably potential for very rapid growth in the world economy over the coming decade, thanks to strong supply-side factors. Whether such growth can be realized depends, however, on demand-side management both at the national level and through improved global macroeconomic policy coordination.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet